Executive Function In Early Childhood: What Do Teachers Know And Do In The Classroom? - Ifana, Fitra; Rahmawati, Yuli; Supena, Asep (UIN Sultan Maulana Hasanudin Banten, 2025)
The purpose of this study is to investigate how early childhood education (ECE) teachers comprehend and use learning techniques that promote the development of executive function in young children. The three primary components of executive functions—working memory, inhibitory control, and cognitive flexibility—are essential to children's self-regulation and preparation for learning. Several early childhood education teachers in the Jakarta and Bekasi regions were interviewed in-depth to gather data using a qualitative methodology. The research findings indicate that most teachers are not familiar with the term